The application of a multidimensional comparative analysis for the short selling of stocks - Flotyński, Marcin (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
In this article the application of the taxonomic measure of investment attractiveness (TMAI) has been presented. It is the element of multidimensional comparative analysis. An empirical study based on the data from the Warsaw Stock Exchange has been conducted. The time scope embraces years 2009–2014 in which different types of market trends occurred. There was a bullish, bearish as well as the horizontal trend. Calculations have been carried out of almost 80 public shares from sWIG80. TMAI value has been computed for each stock on the grounds of financial analysis. It is the synthetic measure which has been estimated on the basis of a dozen financial ratios e.g. asset management, liquidity, profitability, debt management as well as market value ratios. Both have been counted in the research and downloaded from stock market services. All of the ratios have been classified as nominants, stimulants or destimulants. Furthermore, the standardization of variables has been carried out. In the article the “not weighted” type of TMAI has been utilized which means that variables are of the same importance in terms of their final impact on the TMAI’s value. Shares with the lowest values of TMAI have been selected to short-sell portfolio according to the assumption that such stocks are potentially the worst investment assets. The aim of the research is to verify the usefulness of the TMAI method for creating short-sell portfolios. The hypothesis states that the portfolio built on the grounds of stocks with the relatively low TMAI value got comparatively lower rates of return than other portfolios and the market benchmark. The verification of the hypothesis has been done in terms of the rate of return achieved. Such an approach enables an investor to sort financial assets from the best to the worst investments. It occurs that in a period given, the performance of companies with relatively low TMAI was much worse than other firms. The rates of return of such shares were especially low 3 years after they had been purchased.